Pengaruh Lingkungan Kerja dan Beban Kerja Terhadap Kinerja Karyawan pada PT. XYZ di Kabupaten Karawang - Khensa Aqilla Haryanto; Dadan Ahmad Fadili; Asep Maulan (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of the work environment and workload on employee performance, both partially and simultaneously, at PT XYZ in Karawang Regency. The research method used was quantitative with a descriptive and verification approach. The study sample consisted of 263 respondents, determined using the Taro Yamane formula with a probability sampling technique through proportionate stratified random sampling. Data collection was conducted through questionnaires, interviews, and observations. Data analysis used multiple linear regression analysis with the help of SPSS 21, preceded by tests for validity, reliability, normality, multicollinearity, and heteroscedasticity. The results showed that the work environment had a positive and significant effect on employee performance with a calculated t-value of 7.296 and a significance level of 0.000 (<0.05). Workload also had a positive and significant effect on employee performance with a calculated t-value of 14.457 and a significance level of 0.000 (<0.05). Simultaneously, the work environment and workload have a positive and significant effect on employee performance, with a calculated F-value of 356.941 and a significance level of 0.000 (<0.05). They explain 73.1% of the variation in employee performance based on an Adjusted R-Square of 0.731. The conclusion of this study indicates that a conducive work environment and a proportional workload play a significant role in improving employee performance, with workload being the variable with a more dominant influence than the work environment.   Keywords: Workload, Employee Performance, Work Environment